Isolation and structural determination of compounds from Alstonia scholaris (L.) R. Br. (Apocynaceae), collected in Vietnam - Vũ, Trang; Phan Minh Giang; To Phuong Linh (Journal of Military Science and Technology, 2025)
Alstonia scholaris (L.) R. Br. belongs to the genus Alstonia in the family Apocynaceae. For the first time, the current research phytochemically studied on A. scholaris, collected from Vietnam. By silica gel column chromatographic separation, a triterpenoid betulin (1) and a sterol β-sitosterol (3) were found in the ethyl acetate (EtOAc) extract of the leaves. Meanwhile, isolation of the methanol (MeOH) extract of the bark yielded a triterpenoid β-amyrin (2), a sterol β-sitosterol (3) and a free sugar compound sucrose (4). Oxidation of compound 1 with K2Cr2O7 in an acidic medium resulted in betunic acid derivative (1a) with a yield of 43.8%. The structures of these compounds were determined by analysis of spectroscopic data.